(untitled) (World Economics and Finance Bulletin, 2026)
In this paper, we investigate sustainable disclosure as it relates to integrated reporting and the implications for business value. This is to clarify in what, integrated reports can serve the needs of users (i.e., benefit theory), how it would help create/develop enhancement of company-involved value (i.e. creating long-term values) and enlivenment for information constitution. Through measuring the sustainability disclosure in published integrated reports, stakeholders particularly investors will be able to better assess a company’s ability to deliver strong performance now and into the future. Leads to higher share values by increasing investor confidence in sustainability information and willingness to invest. This research is based on a sample of listed Iraqi banks in the Iraq Stock Exchange and depends on financial data by the Iraqi Securities Commission. Sustainability disclosure is used as a strategic tool under the Integrated Reporting Framework, aimed at improving transparency and risk management in addition to building trust and attracting investment that will ultimately contribute to long-term value. Their results show evidence of a linear relationship between the stated Tobin’s Q value of a bank, indicating bank health, and the quality of sustainability disclosures at both the environmental, social and governance (ESG) levels when using Global Reporting Initiative practices. Findings of the Study: Less attention is paid to sustainability indicators, especially where disclosure is limited.